Answer:
b
Step-by-step explanation:
Answer:
The average rate of change is ![=-4](https://tex.z-dn.net/?f=%3D-4)
Step-by-step explanation:
The average rate of change from x=a to x=b of f(x) is given by;
![=\frac{f(b)-f(a)}{b-a}](https://tex.z-dn.net/?f=%3D%5Cfrac%7Bf%28b%29-f%28a%29%7D%7Bb-a%7D)
We want to find the average rate of change of the function represented in the table from x=-2 to x=2.
![=\frac{f(2)-f(-2)}{2--2}](https://tex.z-dn.net/?f=%3D%5Cfrac%7Bf%282%29-f%28-2%29%7D%7B2--2%7D)
From the table f(-2)=25 and f(2)=9
The average rate of change from x=-2 to x=2 is
![=\frac{9-25}{2--2}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B9-25%7D%7B2--2%7D)
![=\frac{-16}{4}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B-16%7D%7B4%7D)
![=-4](https://tex.z-dn.net/?f=%3D-4)
Answer:
The first one
Step-by-step explanation: